NdYAG laser photocoagulation in the dog stomach. Issue 10 (October 1980) - Bown, S G; Salmon, P R; Storey, D W; Calder, B M; Kelly, D F; Adams, N; Pearson, H; Weaver, B M
Abstract : Considerable discussion still centres around the relative merits of the Argon and Neodymium Yttrium Aluminum Garnet (NdYAG) lasers for the endoscopic treatment of gastrointestinal haemorrhage, although both are undoubtedly effect. We have carried out experiments to elucidate which factors determine the safety and efficacy of NdYAG laser photocoagulation. Histological studies on normal gastric mucosa showed that the depth of tissue damage depended mainly on the total incident laser energy, whereas the effectiveness of photocoagulation of induced gastric ulcers in heparinised animals depended on the laser power and the exposure time used. Optimum haemostasis with minimum tissue damage was obtained using pulses of 300 to 500 ms duration with energies of 25 to 40 J. We consider these parameters safe and effective for use in pilot clinical studies.